2014
DOI: 10.1016/j.im.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The continuity of underperforming ICT projects in the public sector

Abstract: The continuity of underperforming ICT projects in the public sector AbstractThere is a growing body of research on the successes and failures of information and communications technology (ICT) projects in the public sector. However, this literature has rarely addressed the question: why do some projects persist and continue despite functioning poorly in several areas. In this paper, we suggest that the notions of institutional logics and status differences provide useful insights into the structure and traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…However, we found that attitude may be influenced by facilitating conditions and social influence, which are the contextual factors in our model. This is perhaps not completely surprising-facilitating conditions such as training programs and help desks may be instrumental in enabling individuals to form positive attitudes about the technology (e.g., Chiu et al 2012;Pynoo et al 2007;Ravishankar 2008;Sahu and Gupta 2007;Sandeep and Ravishankar 2014) whereas individuals may also refine their attitudes based on information or stories shared by others who have already adopted the technology (e.g., Abubakre et al 2015;Chiu et al 2012;Pynoo et al 2007;Sumak et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that attitude may be influenced by facilitating conditions and social influence, which are the contextual factors in our model. This is perhaps not completely surprising-facilitating conditions such as training programs and help desks may be instrumental in enabling individuals to form positive attitudes about the technology (e.g., Chiu et al 2012;Pynoo et al 2007;Ravishankar 2008;Sahu and Gupta 2007;Sandeep and Ravishankar 2014) whereas individuals may also refine their attitudes based on information or stories shared by others who have already adopted the technology (e.g., Abubakre et al 2015;Chiu et al 2012;Pynoo et al 2007;Sumak et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…We adopted the qualitative case study method [28] to generate in-depth accounts and to develop rich insights into the organizational processes supporting technological innovation at Mahindra Reva. We chose to study Mahindra Reva given the novelty and atypical nature of the setting -it is one of the few emerging market companies producing electric vehicles.…”
Section: Methodsmentioning
confidence: 99%
“…Using a mixture of closed-and open-ended questions, it was revealed that while some of the 240 respondents saw increased accountability as a result of e-government, others envisaged the opposite. From the citizen perspective, accountability as a result of e-government may precede trustworthiness of e-government (see Sandeep and Ravishankar 2014).…”
Section: Trustworthiness Of E-government and Associated Variablesmentioning
confidence: 99%
“…Some regard e-government as a powerful tool for improving the internal efficiency of the government, the quality of service delivery, and public participation and engagement Dawes 2008;Gil-García and Pardo 2005;Parent, Vandebeek, and Gemino 2005;Rana and Dwivedi 2015;Rana et al 2015aRana et al , 2016. Others find e-government to be a means of helping to establish trustworthy institutions and building or restoring citizen's trust in government (Bellamy and Taylor 1998;Tolbert and Mossberger 2006;West 2005;Sandeep and Ravishankar 2014).…”
Section: Introductionmentioning
confidence: 99%